A Two‐Dimensional Lamellar Membrane: MXene Nanosheet Stacks - Ding, Li; Wei, Yanying; Wang, Yanjie; Chen, Hongbin; Caro, Jürgen; Wang, Haihui (Angewandte Chemie International Edition, 2017)
Two‐dimensional (2D) materials are promising candidates for advanced water purification membranes. A new kind of lamellar membrane is based on a stack of 2D MXene nanosheets. Starting from compact Ti3AlC2, delaminated nanosheets of the composition Ti3C2Tx with the functional groups T (O, OH, and/or F) can be produced by etching and ultrasonication and stapled on a porous support by vacuum filtration. The MXene membrane supported on anodic aluminum oxide (AAO) substrate shows excellent water permeance (more than 1000 L m−2 h−1 bar−1) and favorable rejection rate (over 90 %) for molecules with sizes larger than 2.5 nm. The water permeance through the MXene membrane is much higher than that of the most membranes with similar rejections. Long‐time operation also reveals the outstanding stability of the MXene membrane for water purification. A lamellar MXene membrane formed of two‐dimensional Ti3C2TX MXene nanosheets (see picture; purple sheets) with colloidal Fe(OH)3 (yellow spheres) as intercalator exhibits an excellent water permeance (more than 1000 L m−2 h−1 bar−1). The membrane, which was formed on anodic Al2O3, also has good stability and a high rejection rate (over 90 %) for molecules with sizes larger than 2.5 nm.